Non-destructive techniques for mitigating losses of fruits and vegetables - Silveira, Ana Cecilia; Rodríguez, Silvia; Kluge, Ricardo; Palaretti, Luiz Fabiano; Inestroza, Carlos; Escalona, Victor H. (Agrociencia Uruguay, 2022)
Fruits and vegetables losses and wastage have massive impacts on the economy, as they constitute about half of the 1.3 billion tons of food annually lost; on the environment, because its elimination generates 10%-12% of greenhouse gases, and on society, because one of every four calories produced is not consumed. Losses are generated during production, postharvest, and marketing periods. In developing countries, only in postharvest, losses reach between 40% and 50% depending on the product considered. Losses can be grouped into physical, biological, and physiological, and their reduction constitutes a challenge that countries are attempting to tackle through both individual and collaborative actions. For applying successful mitigation strategies, not only their quantification but also the identification of factors and occasions in which losses occur are of utmost importance. In this sense, the use of non-destructive techniques is especially useful as such techniques facilitate the detection of physical damages before they are visible or the identification of pathogens before they develop. Other aspects include the possibility of monitoring refrigeration conditions during storage and transport, identifying the occurrence of a cold chain break, and making it possible to rectify the same. In this paper, various techniques applicable to the identification and reduction of losses are reviewed.